2016
DOI: 10.1016/j.chemolab.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Iterative optimization technology combined with wavelength selection based on excess absorption for a process analytical technology calibration–minimum approach

Abstract: a b s t r a c tProcess analytical technology (PAT) plays an important role in the pharmaceutical industry. Calibration-free/ minimum methods in PAT are expected to aid in a deeper understanding of processes in the early development stage of new drugs. Iterative optimization technology (IOT), an existing calibration-free method, is not able to predict the compositions of nonideal mixtures because the Beer-Lambert law does not hold in some wavelength regions. In this paper, we propose IOT with wavelength selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…IOT is not effective when Beer's law does not hold at some wavelengths. The authors have been proposed two types of wavelength selection [Kaneko et al 2015, Shibayama et al 2016. One indicator to determine if Beer's law holds is excess absorbance, which is difference between the observed mixture spectrum and mixture spectrum calculated using eq.…”
Section: Wavelength Selection Based On Excess Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…IOT is not effective when Beer's law does not hold at some wavelengths. The authors have been proposed two types of wavelength selection [Kaneko et al 2015, Shibayama et al 2016. One indicator to determine if Beer's law holds is excess absorbance, which is difference between the observed mixture spectrum and mixture spectrum calculated using eq.…”
Section: Wavelength Selection Based On Excess Absorptionmentioning
confidence: 99%
“…(1). We have found that root mean square of xmix-xmix,pred (RMSE xmix) is an indicator to estimate prediction error in r [Shibayama et al 2016, Shibayama and. Once virtual mixture spectra are generated with eq.…”
Section: Inference Of Errors For Wiotmentioning
confidence: 99%
See 1 more Smart Citation
“…Funatsu et al identified this weakness in the method and proposed two ways to mitigate it. One is to limit the region(s) of the spectra to be included into the analysis using of a genetic algorithm for variable selection, and the other is the modification of the inner relationship in BLL adding a nonlinear term. , The latter extension requires the estimation of a nonlinear pure spectrum and an exponent for the molar fractions.…”
Section: Introductionmentioning
confidence: 99%